OBSSESIVE LOVE OF THE MAIN CHARACTER IN SOLCHE’S CRY, BETTER OR YET, BEG - Rayda Nur Hafishah; Saraswati, Sri; Tetty Harjani, Emilia (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study describes the obsessive love of the main character as seen in the novel Cry, or Better Yet, Beg by Solche. It aims to determine the characteristics of obsessive love experienced by Matthias Von Henhardt as the obsessor and the negative impacts of obsessive love on Layla Llewellyn as the target of obsessive love. The method of collecting data in this research is library research, and the method of analyzing data is descriptive qualitative. The research focuses on a psychological approach. Susan Forward and Craig Buck’s theory was employed to identify the characteristics of obsessive love, while Belton and Bailey's theory was also applied to identify the negative impacts of obsessive love. The results show that the characteristics of obsessive love in the novel are one magic person, rejection, revenge, and the savior complex. Additionally, the negative impacts of obsessive love are stalking and domestic violence. Domestic violence happens in the form of physical abuse, emotional or psychological abuse, and sexual abuse. These results improve understanding of how obsessive love can turn into a toxic relationship as portrayed in popular digital literature.